2015
DOI: 10.3390/molecules201119661
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Density Functional Theory (DFT), Urease Inhibition and Antimicrobial Activities of 5-Aryl Thiophenes Bearing Sulphonylacetamide Moieties

Abstract: A variety of novel 5-aryl thiophenes 4a-g containing sulphonylacetamide (sulfacetamide) groups were synthesized in appreciable yields via Pd[0] Suzuki cross coupling reactions. The structures of these newly synthesized compounds were determined using spectral data and elemental analysis. Density functional theory (DFT) studies were performed using the B3LYP/6-31G (d, p) basis set to gain insight into their structural properties. Frontier molecular orbital (FMOs) analysis of all compounds 4a-g was computed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 25 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…The authors observed a trend in which electron-withdrawing groups were more active at inhibiting the enzyme than their electron-donating counterparts, highlighting the di-halogenated compound ( 44 – Series A; Scheme 16 ) as the most active of the series [68] . Noreen et al also explored the potential of 5-aryl-thiophene-2-sulfonamides, three of which were more active than the positive control, namely compounds 48 and 49 ( Scheme 16 ) [69] .
Scheme 16 Chemical structures of urease inhbitors based on 5-aryl-thiophene-2-carbaldehydes scaffold.
…”
Section: Organic Substances As Urease Inhibitorsmentioning
confidence: 99%
“…The authors observed a trend in which electron-withdrawing groups were more active at inhibiting the enzyme than their electron-donating counterparts, highlighting the di-halogenated compound ( 44 – Series A; Scheme 16 ) as the most active of the series [68] . Noreen et al also explored the potential of 5-aryl-thiophene-2-sulfonamides, three of which were more active than the positive control, namely compounds 48 and 49 ( Scheme 16 ) [69] .
Scheme 16 Chemical structures of urease inhbitors based on 5-aryl-thiophene-2-carbaldehydes scaffold.
…”
Section: Organic Substances As Urease Inhibitorsmentioning
confidence: 99%
“…Among these are hydroxamic corrosive subordinates [ 17 ], hydroxyurea [ 18 ], hydroxamic acids [ 19 ], phosphorodiamidates, imidazoles, for example, rabeprazole, lansoprazole, omeprazole, quinines, thiol derivatives, and phenols, Schiff base and thiourea derivatives [ 20 ]. Sulfonamides constitute an important class of organic compounds that possess a broad spectrum of biological activities such as antibacterial, high-ceiling diuretic, hypoglycemic, antithyroid, anti-inflammatory and antiglaucoma effects [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Noreen et al recently reported thiophene-tagged sulfonamides as µg/mL concentration urease inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Mnaza Noreen used the indoxyl method to determine its inhibitory effect on the urease activity. The results showed that N- ((5-(4-chlorophenyl)thiophen-2-yl)sulfonyl) acetamide at a concentration of 15 µg/mL, IC 50 17.1 µg/mL has a good inhibitory effect on urease, and the inhibition rate is ∼46.23 ± 0.11% (Mnaza et al, 2015). Disulfiram and other compounds containing thiol reactive groups can be used to redesign better and more specific urease inhibitors (Díaz-Sánchez et al, 2016).…”
Section: Chemical Inhibitor and Oxidizermentioning
confidence: 99%